2017
DOI: 10.1016/j.actamat.2017.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Spherical nanoindentation, modeling and transmission electron microscopy evidence for ripplocations in Ti3SiC2

Abstract: Herein we present experimental and modeling evidence for a new deformation micromechanism operating in layered solids termed a ripplocation. Select Ti 3 SiC 2 grains were cyclically indented-either parallel or normal to the basal planes-with spherical tips with radii, R of 21 μm and 100 μm. When the load vs. displacement curves were converted to indentation stress vs. a/R curves, where a is the contact radius, fully and spontaneously reversible hysteresis loops were recorded. The energy dissipated per unit vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…More recently, it has been suggested that in layered materials, including MAX phases, ripplocations and not the basal dislocations are the operative micromechanism of deformation [12]. In principle, the value of τ CRSS needed to move ripplocations will increase with an increase in stress normal to the basal plane [11], which can also give rise to non-classical crystallographic slip shown in Figure 5(b). Thus, more work is needed to confirm the micromechanism of non-classical crystallographic slip in MAX phases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, it has been suggested that in layered materials, including MAX phases, ripplocations and not the basal dislocations are the operative micromechanism of deformation [12]. In principle, the value of τ CRSS needed to move ripplocations will increase with an increase in stress normal to the basal plane [11], which can also give rise to non-classical crystallographic slip shown in Figure 5(b). Thus, more work is needed to confirm the micromechanism of non-classical crystallographic slip in MAX phases.…”
Section: Resultsmentioning
confidence: 99%
“…While MAX phases have only two independent basal slip systems [5][6][7], the existence of additional deformation and failure mechanisms facilitated by their CONTACT Ankit Srivastava ankit.sri@tamu.edu nanolayered structure distinguishes them from other materials with an insufficient number of slip systems. The weakly bonded MX-A interlayers in the MAX phases not only facilitate crystallographic slip but also cleavage, buckling of layers, ripplocations and kinking [3,4,[8][9][10][11][12]. All these additional deformation and failure modes of MAX phases also contribute to their anisotropic mechanical behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new fundamental defect type, named ripplocations, has been proposed, which takes the form of atomic-scale ripples in the basal layer 19 . They have so far been studied and modelled in MoS 2 19 , Ti 3 SiC 2 20,21 and graphite 21,22 but are theoretically applicable to phyllosilicates and other layered solids 23 . Ripplocations have a similar effect to dislocations in that they allow the motion of one plane of atoms over another and may be more favourable in certain crystallographic directions 19,24 , but differ because they do not require the breaking and re-building of in-plane bonds (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Crucially, ripplocations involve a ripple in the basal layers, giving them a component of c -axis parallel strain that is absent in basal dislocations. They have been visualised in transmission electron microscope (TEM) observations of experimentally deformed MoS 2 19 and Ti 3 SiC 2 20,21 , while ripplocation behaviour has been tested through numerical modelling 19,21 . However, prior to this study, ripplocations have not been reported in any naturally occurring mineral.…”
Section: Introductionmentioning
confidence: 99%